MODEL PENGEMBANGAN KEBIJAKAN INTEGRASI SISTEM MANAJEMEN MUTU DAN LINGKUNGAN (STUDI KASUS KAWASAN INDUSTRI JABABEKA, CIKARANG, BEKASI) - Aris Dwi Cahyanto; Bambang Pramudya; Erliza Noor (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2016)
The purpose of this research is to construct an integrated policy development model of quality and environment management system. The whole process runs through several stages: analyzing status of sustainable tenant service, identifying leverage factors, analyzing key factors, and constructing an integrated policy development model of quality and environment management system. Results of this research show that tenant service reviewed from ecological, sociable, technological, institutional dimensions has less-sustainable status. However, when seen from its economical dimension, this tenant service matter is quite sustainable. Multi-dimensional scaling analysis provides results on twenty-three leverage factors which are sensitive to sustainability status. From these leverage factors, prospective analysis is conducted to determine key factors. It is discovered that there are four key factors: area regulations, product development innovations, raw water quantity, and shop houses development. These key factors are essential input for policy development. Researcher applies process hierarchy analysis to construct policy development model. From this model, it is discovered that the most influential actor in the development of quality management and environment system integration policy is area management. Actors pay high attention to economical dimension, but only pay low attention to ecological dimension. Development of quality management and environment system integration policy is directed at the fulfillment of area regulations, as these regulations have the heaviest weight and the highest priority.